The attitude to luxury amongst young Polish and Portuguese consumers - Dryl, Wioleta; Kozłowski, Arkadiusz (Economics and Business Review, 2016)
The aim of this paper is to examine the differences between Polish and Portuguese young consumer attitude to luxury. Studies on the perception of luxury and the consumer attitude to this phenomenon are based on many factors and take into account different sets of variables. The process of changes in this field is very dynamic- and the results obtained are often not compatible with the results of previous studies. Unanimity in this area can be guaranteed only by a comprehensive approach to the problem, based on international, intercultural studies, taking into account factors perceived as being essential for the understanding of consumer attitude to luxury. According to the results of worldwide research carried out so far, the attitude to luxury differs amongst consumers belonging to different cultures, nationalities, religions and regions with different levels of economic development. Many authors emphasize the fact that also psychological variables such as social compliance, desirability and self-monitoring, may play a role in consumer attitude to luxury. The authors of the article conducted a survey amongst young consumer from Poland and Portugal, to test if significant differences occur amongst these two groups’ attitude to luxury.